Analyzing the impact of blood collection errors on patient safety and clinical outcomes⁠ - Almotairi, Wadha A.; Alrashidi, Maha N.; Alqarni, Mohammed A.; Alsubaie, Raghad I.; Alshahrani, Abeer M.; Almuaybid, Rana A.; Al-Johar, Jawaher J.; Najem, Wedian M.; Alharbi, Nawaf A. (International Journal Of Community Medicine And Public Health, 2025)
Errors in blood collection processes pose a significant challenge to healthcare systems, contributing to diagnostic inaccuracies, compromised patient safety, and adverse clinical outcomes. Pre-analytical errors, including patient misidentification, improper labeling, hemolysis, and sample contamination, are among the most common sources of laboratory mistakes. These errors can delay diagnosis, lead to unnecessary medical interventions, and increase healthcare costs. Misidentification and labeling errors, for example, have been linked to life-threatening outcomes in transfusion medicine, while hemolysis often results in falsely elevated laboratory values that can mislead clinical decision-making. Effective strategies to address blood collection errors include leveraging technological innovations, such as barcoding systems and automated labeling, which have demonstrated success in reducing mislabeling incidents. Adherence to standardized guidelines, including protocols established by the Clinical and Laboratory Standards Institute (CLSI), plays a crucial role in maintaining sample integrity. Additionally, phlebotomy training programs and competency assessments ensure that healthcare staff consistently follow best practices, minimizing errors during the collection process. Quality management tools, including Six Sigma and Lean methodologies, further enhance laboratory processes by identifying root causes of errors and implementing targeted improvements. Patient engagement also contributes to error prevention, with informed and active participation serving as an additional safeguard against potential mistakes. The integration of these strategies has shown promise in improving diagnostic reliability and reducing the clinical and economic burden of blood collection errors. By addressing systemic, procedural, and technological factors, healthcare systems can ensure safer and more accurate diagnostic practices, ultimately enhancing patient outcomes. A multidisciplinary focus remains essential for achieving sustainable improvements in blood collection processes and mitigating risks associated with pre-analytical errors.